Synthesis of 2,3-Disubstituted Carbazoles, Benzo[c]carbazoles, and Phenanthrenes Through FeCl3-Mediated Cyclization of Triene Frameworks - Raju, Potharaju; Mageshwaran, Thiyagarajan; Ramalingam, Bose Muthu; Mohanakrishnan, Arasambattu K. (SynOpen, 2018)
A facile synthesis of 2,3-disubstituted carbazoles through electrocyclization of 2,3-divinylindoles using FeCl3 in DMF at reflux is reported. The methodology was found to be applicable for smooth transformation of 3-aryl-2-vinylindole as well as 2-styrylbiphenyl into the respective benzo[c]carbazole and phenanthrene.
Keywords: carbazoles; electrocyclization; Iron(III) chloride; 2,3-divinylindole; benzocarbazole; phenanthrene